Viral hepatitis a clinical guide - Jilg, Wolfgang
"Viral hepatitis : a clinical guide" reviews the clinical aspects of acute and chronic viral hepatitis, the etiologic agents, their epidemiology as well as the possibilities for immunoprophylaxis and therapy